A STUDY TO ASSESS THE IMPACT OF FOOTFALLS AND CATEGORY MIX ON MALL PERFORMANCE - Joshi, Krishan; Gupta, Sachin (International Journal of Engineering Technologies and Management Research, 2018)
Shopping centers have become a center of convergence providing an opportunity to shop, entertain, relax and socialize. The quantum of foot traffic to the mall indicates the preference of the customers to visit a specific mall as the customers believe that their interests will be best met there in terms of ambiance, shopping, facilities and convenience. Though, footfalls indicate preference but it does not anyway relate to actual conversions because there are many other parameters that influence their buying decision. On the other hand, presence of diverse categories inside the mall helps in their decision to buy as the customers want multiple engagements for his family besides shopping at one place. This study aims to find which impacts more footfalls or presence of category mix on the performance of the mall.